2020
DOI: 10.13057/biodiv/d210727
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mycoinsecticides and abamectin applications on species diversity and abundance of aquatic insects in rice fields of freshwater swamps of South Sumatra, Indonesia

Abstract: Abstract. Herlinda S, Alesia M, Susilawati, Irsan C, Hasbi, Suparman, Anggraini E, Arsi. 2020. Impact of mycoinsecticides and abamectin applications on species diversity and abundance of aquatic insects in rice fields of freshwater swamps of South Sumatra, Indonesia. Biodiversitas 21: 3076-3083. Aquatic insects in rice fields generally are predators of rice insect pests. The application of insecticides may reduce the abundance and species diversity of these predators. This study aimed to determine the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In the rice PI-100 and PI-200, the species diversity of the soil-dwelling predatory arthropods was lower due to the dominance of species of P. occipitalis and P. pseudoannulata. The spraying insecticides on the surface of the soil and water can reduce the arthropod species diversity, particularly those that are sensitive can be killed (Hanif et al 2020;Herlinda et al 2020a). However, in this study, the intensive spraying of synthetic insecticides was not only 2-3 times during one rice planting season, even though the rice PI-200 and PI-300 were applied with the synthetic insecticides, but it also did not reduce the species diversity of the soil-dwelling predatory arthropods.…”
Section: Discussionmentioning
confidence: 59%
“…In the rice PI-100 and PI-200, the species diversity of the soil-dwelling predatory arthropods was lower due to the dominance of species of P. occipitalis and P. pseudoannulata. The spraying insecticides on the surface of the soil and water can reduce the arthropod species diversity, particularly those that are sensitive can be killed (Hanif et al 2020;Herlinda et al 2020a). However, in this study, the intensive spraying of synthetic insecticides was not only 2-3 times during one rice planting season, even though the rice PI-200 and PI-300 were applied with the synthetic insecticides, but it also did not reduce the species diversity of the soil-dwelling predatory arthropods.…”
Section: Discussionmentioning
confidence: 59%
“…Some previous studies on arthropods in rice field ecosystems in Indonesia have been reported (Karenina et al 2019;Prabawati et al 2019;Herlinda et al 2020;Wakhid et al 2020). Prabawati et al (2019) reported that the abundance of canopy arthropods in South Sumatra (Indonesia) freshwater swamp main and ratooned rice applied with bioinsecticides and synthetic insecticide.…”
Section: Introductionmentioning
confidence: 96%
“…Karenina et al (2019) showed that herbivore population and the lowest of spiders abundance in rice field ecosystems with synthetic insecticide application and significantly different with population in rice field ecosystems with refugia. The lowest of predatory insect abundance in plots with Abamectin applications reduced the parasitoid and herbivore number in freshwater swamps 5851 of South Sumatra, Indonesia (Herlinda et al 2020). Furthermore, the aquatic insect community in rice field ecosystems also reported in Bogor, West Java, Indonesia (Wakhid et al 2020).…”
Section: Introductionmentioning
confidence: 99%